Cultural Crossroads: The Dilemmas of Identity and Assimilation of Bangladeshi Immigrants in the United Kingdom in Monica Ali’s Brick Lane (2003) - Rezzoug, Meriem; Benaya, Amina Yasmine; Kourdourli, Abdelkader (Faculty of Letters and Foreign Languages Department of English, 2023)
This dissertation delves into the intricate theme of Bangladeshi immigrants identity within the UK's cultural landscape. It explores how individuals navigate dual backgrounds, addressing key issues like identity crises, discrimination, generational shifts, religion, language, and cultural influence. The focal point is the case study of Monica Ali's Brick Lane, shedding light on the challenges and triumphs in identity formation. The research uncovers a persistent identity crisis, influencing assimilation outcomes. This study aims to highlight the fact that identity crisis of immigrants is ongoing, same as the struggle for adaption that they encounter due to the antagonism between their cultural background and the culture of the hosting community. Through analytical-qualitative methods, the main findings of this study reveal three distinct groups: seamless assimilation, profound identity crisis leading to failed adaption, and successful assimilation while preserving cultural heritage, forming a hybrid identity. This study contributes to the fields of identity studies, literature, and cultural studies by offering a thorough analysis of Bangladeshi immigrants identity and its difficulties within the setting of Brick Lane. It improves the knowledge of this particular community while also providing insightful information that can be used in the more general study of identity, immigration, and integration in multicultural societies